Theory of planned behavior and adherence in chronic illness: a meta-analysis - Rich, A.; Brandes, K.; Mullan, Barbara; Hagger, Martin (Springer New York LLC, 2015)
Social-cognitive models such as the theory of planned behavior have demonstrated efficacy in predicting behavior, but few studies have examined the theory as a predictor of treatment adherence in chronic illness. We tested the efficacy of the theory for predicting adherence to treatment in chronic illness across multiple studies. A database search identified 27 studies, meeting inclusion criteria. Averaged intercorrelations among theory variables were computed corrected for sampling error using random-effects meta-analysis. Path-analysis using the meta-analytically derived correlations was used to test theory hypotheses and effects of moderators. The theory explained 33 and 9 % of the variance in intention and adherence behavior respectively. Theoretically consistent patterns of effects among the attitude, subjective norm, perceived behavioral control, intention and behavior constructs were found with small-to-medium effect sizes. Effect sizes were invariant across behavior and measurement type. Although results support theory predictions, effect sizes were small, particularly for the intention-behavior relationship.